Från realism till post-sanning och tillbaka igen? Nyhetsbransch, museer och högre utbildning mot fejkade nyheter och faktaresistens - Carlsson, Eric; Carbin, Maria; Nilsson, Bo (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2018)
Recently, the problem with fake news, fact resistance and the growing digital, global circulation of disinformation have caused debates and worries, and posed a challenge for several institutions of knowledge in society. In this article, we discuss how the news industry, museums and higher education confront the challenges of the ‘post truth’ era. We can see a mobilization by these institutions in Sweden: The news industry has initiated so-called fact checking sites, the major museums create exhibitions about false news and educate youth in digital literacy and many universities have launched initiatives to legitimize scientific knowledge production, thereby safeguarding professional authority. However, these initiatives are faced with dilemmas concerning how concepts of knowledge, truth and facts are negotiated and understood. This article discusses such epistemological issues in general, and focuses in particular on the risk of falling into the trap of so called neorigorism.